2020
DOI: 10.1002/zaac.202000219
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Explosive Energy Output by EXPLO5 Thermochemical Code

Abstract: Detonation velocity, detonation pressure, and detonation heat are usually used as a measure of explosive's performance. However, they do not answer the question how fast an explosive can accelerate the surrounding metal liner. A semi‐empirical solution to this problem was proposed by R. W. Gurney in 1943. In this paper we used thermochemical calculations to calculate energy of detonation products along the expansion isentrope and to estimate the Gurney energy and cylinder wall velocity from it. It was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…Our previous studies have shown that at the same expansion ratio, detonation energies calculated by EXPLO5 code are systematically ∼10% higher than the Gurney energies derived from experimental cylinder wall velocities [15, 16]. Similar results are reported also by Hardesty and Kennedy [17] and by Danel and Kazandijan [5] who used different thermochemical codes.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Our previous studies have shown that at the same expansion ratio, detonation energies calculated by EXPLO5 code are systematically ∼10% higher than the Gurney energies derived from experimental cylinder wall velocities [15, 16]. Similar results are reported also by Hardesty and Kennedy [17] and by Danel and Kazandijan [5] who used different thermochemical codes.…”
Section: Resultssupporting
confidence: 83%
“…This partly explains the energy difference between the Gurney model and hydro‐code calculations. The results reported in [16], as well as the results shown in Figure 2, suggest that the overall energy losses accounts for about 10% of the total energy. The easiest way to take into account energy losses is to reduce calculated detonation energy in the Gurney equation (Eq.…”
Section: Methodsmentioning
confidence: 55%
See 3 more Smart Citations